2007
DOI: 10.15517/rbt.v56i3.5704
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ovarian growth in Aegla platensis (Crustacea, Aeglidae) by means of neuroregulators incorporated to food

Abstract: The freshwater crab Aegla platensis was used as a model to induce ovarian growth by adding different neuroregulators to a pellet food formulation. Added compounds were the dopaminergic inhibitor spiperone or the enkephalinergic inhibitor naloxone, both of them at a dose of 10-8 mol/animal. Animals were fed on the enriched pellets twice a week. After 7 wk, the gonadosomatic index (GI) was calculated as (gonad fresh weight / body fresh weight) x 100. GI significantly increased only for those females fed on spipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
(20 reference statements)
0
7
0
2
Order By: Relevance
“…Administration of 5-HT plus spiperone as well as spiperone alone stimulated ovarian maturation and embryonic development, and increased ovarian index and oocyte diameters in M. rosenbergii (Tinikul et al, 2009b). In vivo spiperone treatment has also been reported to stimulate ovarian maturation in crayfish Cherax quadricarinatus and subsequently produced an augmented percentage of spawning females (Cahansky et al, 2008). Cahansky and colleagues also reported that gonadosomatic index (GSI) in Aegla platensis was stimulated by food containing spiperone (Cahansky et al, 2008).…”
Section: Role Of Neurotransmitters In Reproductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Administration of 5-HT plus spiperone as well as spiperone alone stimulated ovarian maturation and embryonic development, and increased ovarian index and oocyte diameters in M. rosenbergii (Tinikul et al, 2009b). In vivo spiperone treatment has also been reported to stimulate ovarian maturation in crayfish Cherax quadricarinatus and subsequently produced an augmented percentage of spawning females (Cahansky et al, 2008). Cahansky and colleagues also reported that gonadosomatic index (GSI) in Aegla platensis was stimulated by food containing spiperone (Cahansky et al, 2008).…”
Section: Role Of Neurotransmitters In Reproductionmentioning
confidence: 98%
“…Naloxone, an antagonist of enkephalinergic receptors, can stimulate ovarian growth in both U. pugilator and P. clarkii (Sarojini et al, 1995a). Cahansky and colleagues (Cahansky et al, 2008) reported that ovarian maturation in A. platensis was stimulated by food containing naloxone. Kishori and Reddy (Kishori and Reddy, 2003) found an antagonistic action of opioid peptides in the regulation of ovarian maturation in the crab Oziotelphusa senex senex.…”
Section: Role Of Opioid Peptides In Crustacean Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quando injetada durante o início da vitelogênese, a spiperona também produziu um aumento no índice gonadossomático em P. clarkii (100 µl) (RODRÍGUEZ et al, 2002a) e em N. granulata (50 µl) (ZAPATA et al, 2003). Em A. platensis Schmitt, 1942, o efeito da spiperona sobre a estimulação do desenvolvimento ovariano foi observada quando a mesma foi incorporada ao alimento (CAHANSKY et al, 2008).…”
Section: Resultsunclassified
“…Resultados de estudos utilizando a naloxana como neuroregulador mostraram que este é capaz de induzir a maturação dos ovários do caranguejo estuarino Uca pugilator (Bosc, 1802) , no lagostim P. clarkii (SAROJINI et al, 1996) e também em A. platensis (CAHANSKY et al, 2008). Em A. uruguayana, tanto a spiperona como a naloxana causaram indução ovariana, sendo esta indução mais pronunciada quando foi utilizada a spiperona.…”
Section: Discussionunclassified